2009
DOI: 10.1007/s12161-009-9082-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Real-Time PCR and Enzyme-Linked Fluorescent Assay-Based Methods for Detection of Salmonella spp. in Chicken Feces Samples

Abstract: A comparative study of enzyme-linked fluorescent assay (ELFA)-based methods and real-time polymerase chain reaction (PCR)-based methods using three and two different sample preparation protocols, respectively, and the standard culture-based method EN ISO 6579:2002/ Amd1:2007, for the detection of Salmonella spp. in chicken feces, was performed on 20 artificially and 68 naturally contaminated chicken feces. Selectivity, relative specificity, relative accuracy, relative sensitivity, and relative detection level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…[8], Salmonella spp. [23] and L. monocytogenes [24], or multipathogen detection [1,9,25]. Multipathogen detection on a single-assay platform not only reduces the cost for testing but also provides data on the presence of pathogens in a single experiment [26].…”
Section: Introductionmentioning
confidence: 99%
“…[8], Salmonella spp. [23] and L. monocytogenes [24], or multipathogen detection [1,9,25]. Multipathogen detection on a single-assay platform not only reduces the cost for testing but also provides data on the presence of pathogens in a single experiment [26].…”
Section: Introductionmentioning
confidence: 99%
“…in animal feces and in samples from the primary production stage is International Organization for Standardization (ISO) method 6579:2002/Amd 1:2007(ISO, 2007 in the countries of the European Union, and this method also involves 4 to 6 d. To shorten this detection time in the interest of layer companies, realtime PCR (rPCR) can be applied to fecal samples before culture results (Eyigor et al, 2002;Kurowski et al, 2002;Eyigor and Carli, 2003;Eriksson and Aspan, 2007;Tomás et al, 2009;Hadjinicolaou et al, 2009). However, as has been previously pointed out (Eyigor et al, 2002), the fact that rPCR and culture can complement each other and cannot replace one another should always be kept in mind.…”
Section: Introductionmentioning
confidence: 99%
“…The erroneous selection of the colonies for further confirmation tests may have been the cause of the false-negative results. Some authors have suggested that the multistaged nature of testing and subjective readings based on visual color changes may prompt mistakes in interpreting the results (Tomás et al, 2009). Ö zer and Kimiran-Erde (2013) and Vieira-Pinto (2005) had a different explanation for the higher number of positive results generated by the FISH technique in comparison with the standard method.…”
Section: Discussionmentioning
confidence: 99%